2010
DOI: 10.1111/j.1600-0625.2009.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of narrowband UVB phototherapy on vitamin D and folate status

Abstract: Background: A variety of studies have shown beneficial effects of different types of phototherapy in skin disorders. Such therapy leads to enhanced cutaneous vitamin D synthesis, which may be one of the mechanisms of action. Furthermore, another nutrient, folate, can probably also be influenced by UV radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 43 publications
(58 reference statements)
11
62
0
Order By: Relevance
“…16 Our observation that individuals with low initial concentrations of 25(OH)D have a higher response to UVBnb irradiation confirmed previous reports. 4,11,17 We did not find any correlation between the cumulative dose of UVBnb and the increase of serum 25(OH)D at 12 weeks, in accordance with Osmancevic et al 14 but in contradiction to a recent study. 18 The explanation might be that 25(OH)D reaches a plateau after 3 weeks already, and that exposure to additional UVBnb may not result in a continued proportional increase in serum vitamin D. UVBnb therapies but significant only under UVBbb therapy.…”
Section: -15supporting
confidence: 72%
“…16 Our observation that individuals with low initial concentrations of 25(OH)D have a higher response to UVBnb irradiation confirmed previous reports. 4,11,17 We did not find any correlation between the cumulative dose of UVBnb and the increase of serum 25(OH)D at 12 weeks, in accordance with Osmancevic et al 14 but in contradiction to a recent study. 18 The explanation might be that 25(OH)D reaches a plateau after 3 weeks already, and that exposure to additional UVBnb may not result in a continued proportional increase in serum vitamin D. UVBnb therapies but significant only under UVBbb therapy.…”
Section: -15supporting
confidence: 72%
“…Level of vitamin D decreased after treatment in 3 patients (2 males and 1 female) with the initial normal level of vitamin D, which was at the normal range for male patients, but it was inadequate in the female patient; and this was consistent with previous studies (13,14). Such a similar relationship in response to 25 (OH) D to radiation and its relationship with initial level of 25 (OH) D in a study is seen in our sun bed in healthy individuals as well, but it was not associated with body mass index, oral intake of vitamin D, and gender.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 90%
“…Only 10% to 15% of the 7-Dehydrocholesterol can be converted into the previtamin D in response to sunlight. Some believe that only 7% of 7-Dehydrocholesterol can be converted into the previtamin D. Thus, it seems that the availability of the substrate may be variable: people with a base level lower than 25 (OH) D, which could also increase in response to UVB, have more availability of substrate compared to those with a higher base level of 25 (OH) (13).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The increase in 25(OH)D was higher in the BUVB treated patients when compared to the NBUVB (p=0.008) and heliotherapy (p=0.017) treated groups. Low-dose NBUVB treatment significantly increased vitamin D status in patients with psoriasis, atopic eczema and other skin disorders with low initial levels of 25(OH)D (60,61). Within the following intervention studies, age showed no correlation with the observed increase in 25(OH)D levels (57,58,62).…”
Section: The Effects Of Phototherapy On Vitamin D Status In Patients mentioning
confidence: 87%